A new indigenous community seedbank for everyone in Cumbal, Colombia - Vernooy, Ronnie; Ramirez, Marleni; Chiran Chiran, Jorge Humberto; Gangotena Rosero, Esteban Julian; Nestor, Romero Perilla; Odjo, Sylvanus; Cardona, Olga Perez; Caicedo, Claudia Villota; Urrea-Benítez, José Luis (2024)
In the lush highlands of southern Colombia, farmers face pressing challenges in seed and food security, compounded by falling crop diversity and limited seed exchange between farmers. In response, a new community seedbank aims to conserve local seeds, enrich agrobiodiversity and foster seed and knowledge exchange among local farmers. With a focus on Indigenous culture and education, the seedbank will support healthy and diverse food production, local food sovereignty, and increase the next generation's understanding of the importance of agrobiodiversity.